Desidratação térmica de resíduos de placas de gesso em forno contínuo de elemento móvel helicoidal. - Mendonça, Raelson Salvino de (2015)
In Brazil the treatment of demolition waste and construction (DRC), is an environmental issue rarely addressed, especially gypsum waste. However with change of Resolution N° 307, of CONAMA which established new classification for plaster Waste,of waste type C to Waste type B. It represented a slow but progressive quest for rationalization of constructive processes to lower costs of constructions and increase productivity. in this work conditions of temperature, pressure and time, required to produce recycled beta gypsum from waste of blocks and plates plaster were investigated. were calcined under constant pressure and temperature, varying only the reaction time, 6 samples of gypsum waste. tests will verify values of the water of hydration to confirm the attainment of conversion of the reaction. With the results obtained are determined the kinetic parameters of the reaction for the production of recycled gypsum beta.